The Semitic "Perfect" and the Problem of the Third Person Zero Morpheme. - PAT-EL, NA'AMA (Journal of the American Oriental Society)
In many languages, third person forms in a verbal paradigm are unmarked, and scholars have suggested that such cases are either a result of loss or nondevelopment. In this paper I will argue that in the perfect/stative paradigm in Semitic, the third person morphology is a result of nondevelopment. I suggest that these forms are constructed as predicative adjectives, without person markers, because Semitic never developed third person nominative pronouns. I further discuss other innovative verbal formations in Semitic and show that when subject clitics are noncanonical, for example in Neo-Aramaic, third person forms are clearly marked.